حصر وتصنيف النحل البري المؤبر لأزهار الأشجار المثمرة في بعض قرى القلمون- سورية - البراقي, علي; خالد, باسم (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث في ثلاث من قرى القلمون (حوش عرب، عسال الورد، رنكوس) في محافظة ريف دمشق خلال 2007 - 2005 بهدف إجراء حصر وتصنيف لأهم أنواع النحل البري المؤبر لأهم الأشجار المثمرة (اللوز، المشمش، الكرز، الأجاص، التفاح) وتقدير كثافتها العددية وتحديد العوائل النباتية. أوضحت نتائج الدراسة وجود سبعة أنواع مختلفة من النحل البري تتبع ستة أجناس وأربع فصائل تابعة لفوق فصيلة Apoidea من رتبة غشائية الأجنحة Hymenoptera وهي: Osmia sp.، Andrena spp.، Eucera sp.، Xylocopa sp.، Anthophora sp، Dasypoda sp. بينت النتائج أن هذه الأنواع وحيدة الجيل عدا النوع التابع للجنس Xylocopa، كما أظهر التحليل الإحصائي تفوق النوع التابع للجنس Eucera على بقية الأنواع الأخرى. A research was performed in Damscus countryside province in three villages of AlKalamoun (Hosh Arab, Esal Alward and Rankous) in 2005 – 2007. The work aimed at surveying and classifying the most important species of wild bees pollinating the most important fruit tree species (Almond, Apricot, Cherry, Pear and Apple). Evaluation of their numeral density and definitions of their plant hosts were provided. The study showed that there are seven different species of wild bees which relate to six genera and four families, which related to Apoidea super family Hymenoptera order. The species are Osmia sp., Andrena spp., Eucera sp., Xylocopa sp., Anthophora sp. and Dasypoda sp. The result illustrated also that those species had one generation blooming except the species belonging to the Xylocopa. The statistic analysis showed that the species belonging to Eucera was more abundant than the other species.